Stress Induced by Fishing in Common Octopus (Octopus vulgaris) and Relative Impact on Its Use as an Experimental Model - Valeria Maselli; Mariangela Norcia; Bruno Pinto; Emanuela Cirillo; Gianluca Polese; Anna Di Cosmo (Animals)
The common octopus (Octopus vulgaris), among coleoid cephalopods, has evolved the most complex nervous system and sophisticated behaviors. Historically, O. vulgaris was a key animal model for neurophysiology research, and today, it is studied for its genomic innovations. However, unlike other models, there is no octopus farming for research, so specimens must be collected from the wild. This study assessed the impact of fishing on octopuses used in research, considering those caught using artisanal pots in the ‘Regno di Nettuno’ Marine Protected Area, Ischia (NA). To evaluate fishing stress, we identified morphological stress indicators such as chromatophore pattern and posture, and three potential molecular markers, estrogen receptor (ER), catalase (CAT), and heat shock protein (HSP70). We measured the percentage of stress signals shown by fished specimens and analyzed their differential gene expression. The transcriptional levels of octopuses caught using traps were compared to control specimens acclimated in captivity. Results indicated fluctuations in gene expression due to fishing stress. These findings suggest that an acclimation period after the stress event of fishing is crucial for ensuring the welfare of octopuses used in research, thus enhancing the quality of physiological and ethological studies.